A finite element study on stress distribution of two different attachment designs under implant supported overdenture - Mohamed I. El-Anwar; Salah A. Yousief; Tarek A. Soliman; Mahmoud M. Saleh; Wael S. Omar (Saudi Dental Journal)
Objective: This study aimed to evaluate stress patterns generated within implant-supported mandibular overdentures retained by two different attachment types: ball and socket and locator attachments. Materials and methods: Commercial CAD/CAM and finite element analysis software packages were utilized to construct two 3D finite element models for the two attachment types. Unilateral masticatory compressive loads of 50, 100, and 150 N were applied vertically to the overdentures, parallel to the longitudinal axes of the implants. Loads were directed toward the central fossa in the molar region of each overdenture, that linear static analysis was carried out to find the generated stresses and deformation on each part of the studied model. Results: According to FEA results the ball attachment neck is highly stressed in comparison to the locator one. On the other hand mucosa and cortical bone received less stresses under ball and socket attachment. Conclusions: Locator and ball and socket attachments induce equivalent stresses on bone surrounding implants. Locator attachment performance was superior to that of the ball and socket attachment in the implants, nylon caps, and overdenture. Locator attachments are highly recommended and can increase the interval between successive maintenance sessions. Keywords: Ball and socket attachment, Locator attachment, Finite element analysis, Implant supported overdenture